2020
DOI: 10.3390/jrfm13090194
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Epidemiological Determinants of COVID-19 Pandemic Related to Social and Economic Factors Globally

Abstract: The COVID-19 pandemic has manifested more than a health crisis and has severely impacted on social, economic, and development crises in the world. The relationship of COVID-19 with countries’ economic and other demographic statuses is an important criterion with which to assess the impact of this current outbreak. Based on available data from the online platform, we tested the hypotheses of a country’s economic status, population density, the median age of the population, and urbanization pattern influence on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 52 publications
(41 reference statements)
1
37
0
Order By: Relevance
“…Previous studies have indicated that the epidemic intensity had trivial dependencies on population scale [2,23]. In order to reduce this effect, the daily confirmed cases and deaths in population size of 100,000 were set as the initial data for data processing.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that the epidemic intensity had trivial dependencies on population scale [2,23]. In order to reduce this effect, the daily confirmed cases and deaths in population size of 100,000 were set as the initial data for data processing.…”
Section: Plos Onementioning
confidence: 99%
“…These make population density and the amount of interactions with other people in super large-and very large-sized cities are higher than those of other cities [45]. According to the theory of infectious disease, the increases of population density and the amount of interactions with other people will improve the transmission risk of the epidemic [2,23,39,46]. As a result, novel coronavirus would spread faster in super large-and very large-sized cities, resulting in the large number of CCOPSPTT.…”
Section: Relationship Between City Types and The Confirmed Cases And Deaths Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the effects of the restrictions imposed by the national governments pushed the global economy into the worst recession since the Second World War. Initially, it was the supply shock that concerned the Chinese market (along with conspicuously significant consequences on the international market as well), although the rapid spread of the virus later caused a dramatic decline in demand as well, which deeply disrupted the consumption patterns and investments in every region in the world [7][8][9][10][11].…”
Section: Pandemic Aspectsmentioning
confidence: 99%
“…Zhu et al (2020) reported that children are the index case of only three out of 31 household clusters. Conversely, adult cases have shown higher probabilities of hospitalisation and a need for an ICU bed as well as case fatality rates partially due to compromised immune system with age, meaning they are more likely to suffer from COVID-19 (Gao et al 2020;Hassan et al 2020). According to Verity et al (2020), on which Ferguson et al (2020) based their simulation model, the hospitalisation and case fatality rate increases with age in China.…”
Section: Literature Reviewmentioning
confidence: 99%